Use of ultrasmall superparamagnetic iron oxide particles for imaging carotid atherosclerosis. (October 2015) - Usman, Ammara; Sadat, Umar; Patterson, Andrew J; Tang, Tjun Y; Varty, Kevin; Boyle, Jonathan R; Armon, Mathew P; Hayes, Paul D; Graves, Martin J; Gillard, Jonathan H
Based on the results of histopathological studies, inflammation within atherosclerotic tissue is now widely accepted as a key determinant of the disease process. Conventional imaging methods can highlight the location and degree of luminal stenosis but not the inflammatory activity of the plaque. Iron oxide-based MRI contrast media particularly ultrasmall supermagnetic particles of iron oxide have shown potential in assessing atheromatous plaque inflammation and in determining efficacy of antiatherosclerosis pharmacological treatments. In this paper, we review current data on the use of ultrasmall superparamagnetic iron oxides in atherosclerosis imaging with focus on ferumoxtran-10 and ferumoxytol. The basic chemistry, pharmacokinetics and dynamics, potential applications, limitations and future perspectives of these contrast media nanoparticles are discussed.